Review on Post Pandemic Female Buying behavior with regard to Personal Care products. - Rudrabhatla Prasanna (AG Volumes, 2022)
In India, the country with the second-highest population in the world, a nationwide lockdown was implemented in March 2020 to prevent the spread of COVID-19. Phased reopening of businesses and institutions started in July 2020 once the lockdown was lifted. It should come as no surprise that women are adjusting their behaviours to be more in line with the circumstances they now find themselves in, which include homeschooling, maintaining relationships, and working. During this unusual time, women may find themselves with an abundance of free time or with no time at all. These shifts in behaviour are not limited to how women deal with the challenges of maintaining a healthy work-life balance during a period of quarantine; they also include how they navigate shopping for vital and non-essential products for themselves, their spouses, and their kids. Because of concerns about public health, nations all over the globe are now in the precarious situation of having to choose between preserving lives and protecting people’s means of subsistence.